2015
DOI: 10.1038/srep17533
|View full text |Cite
|
Sign up to set email alerts
|

The isolation and characterization of CTC subsets related to breast cancer dormancy

Abstract: Uncovering CTCs phenotypes offer the promise to dissect their heterogeneity related to metastatic competence. CTC survival rates are highly variable and this can lead to many questions as yet unexplored properties of CTCs responsible for invasion and metastasis vs dormancy. We isolated CTC subsets from peripheral blood of patients diagnosed with or without breast cancer brain metastasis. CTC subsets were selected for EpCAM negativity but positivity for CD44+/CD24− stem cell signature; along with combinatorial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 46 publications
2
96
0
1
Order By: Relevance
“…CTCs showed the matched TP53 R248W mutation with the patient′s tissue tumor although a heterogeneity within CTCs. The results from one recent study showed the extreme heterogeneity of the mutational status of single CTCs in metastatic breast cancer patients [23], there is also a discordance between the mutational status of the primary tumor and CTCs among three analyzed patients. Enriched CTCs using the CellSearch method followed by DEPArray™ sorting for the molecular profiling of single CTCs has been recently reported [22,23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTCs showed the matched TP53 R248W mutation with the patient′s tissue tumor although a heterogeneity within CTCs. The results from one recent study showed the extreme heterogeneity of the mutational status of single CTCs in metastatic breast cancer patients [23], there is also a discordance between the mutational status of the primary tumor and CTCs among three analyzed patients. Enriched CTCs using the CellSearch method followed by DEPArray™ sorting for the molecular profiling of single CTCs has been recently reported [22,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The DEPArray™ technology (Silicon Biosystems, San Diego, CA, USA) is the ideal system to collect pure CTCs for further molecular characterization. Recent studies showed a workflow that enables isolation and molecular characterization at single CTCs, which highlight the potential clinical utility for diagnostic molecular profiling in precision medicine [22,23,24]. The CTCs have been enriched from large population of red blood cells (RBCs) and white blood cells (WBCs) before single-cell sorting processing with DEPArray™ technology.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is essential to model dormancy by studying cancer patients beyond the analysis of Kaplan–Meier plots and by isolating CTCs and DTCs and performing single-cell analysis to investigate dormancy markers (Chery et al, 2014; Sosa et al, 2015; Vishnoi et al, 2015). This summary indicates that there are multiplicities of models to extract information related to dormancy that can be validated in human samples.…”
Section: Models To Study Tumor Cell Dormancymentioning
confidence: 99%
“…EpCAM-negative breast cancer CTCs containing stem-cell properties (CD44 +/CD24−) have been isolated by multiparametric flow cytometry from blood of breast cancer patients. These cells possessed high competence to generate breast cancer brain metastasis in xenografts [138,139]. Incidentally, breast cancer is the second most common cancer to metastasize to the brain and the prognosis of patient diagnosed with brain metastasis remains poor [140].…”
Section: Methods To Isolate and Identify Ctcmentioning
confidence: 99%